Hijaukan Pekarangan, Sejahterakan Keluarga: Inovasi Holtikultura Berkelanjutan di Desa Ngadisari - Rosyihuddin, Muhammad; Hendra, Joni (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Ngadisari Village, which is located in Sukapura Sub-district, Probolinggo Regency, possesses significant agricultural potential, yet it is constrained by geographical conditions, particularly rain-fed land. The majority of its residents rely on farming as their primary livelihood, despite having relatively low levels of education and income. This community service initiative aims to empower local farmers through education in environmentally friendly horticultural cultivation, enhanced farm business management, and increased understanding of the importance of basic accounting practices. The methods employed included lectures, interactive discussions, and hands-on training on marketing strategies and the preparation of simple financial reports. The results indicate a high level of enthusiasm among participants, along with increased knowledge and awareness regarding the importance of managing agricultural enterprises in a modern and sustainable manner. This programme has successfully instilled the understanding that farming involves not only planting and harvesting but also requires strategic marketing and accounting in order to make a tangible impact on household welfare. This initiative stands as a concrete example of a green transformation turning home gardens into productive and competitive plots. It is hoped that this practice can be replicated in other regions with similar conditions.